(3GdehGRfI GdYGeI ddOhdI hGdSjGSGJ GdGbJUGOjI s (3efGgL, JLOjO h GJLGgGJ eYGUQIs - (3bOj(B, (3YHO GdeLjOs ((3JdeSGfs (3GdfTQ GdLGeYj GdLOjOs, 2022)
(3GdehGRfI GdYGeI ddOhdI (B: (3GdeHGOF h GdGYOGO h GdJfajP, GdehGRfI GdYGeI h fTGWGJ GdOhdI , GdGWGQ GdbGfhfj ddehGRfI GdYGeI , ehGRfI GdHfhO , ehGRfI GdHQGeL h GdCOGA , ehGRfI GdJNWjW h GdHQeLI , GdehGRfI GdUaQjI, GdehGRfI GdJYGbOjI , ehGRfI GdLeGYGJ GdeMdjI , JQTjO GdfabGJ GdYGeI h GdGfVHGW GdeGdj, TadajI GdehGRfI GdYGeI , YLR GdehGRfI GdYGeI h CSGdjH GdYdGL , GdGSJOGeI GdehGRfjI(B((3GdeGdjI(B)(3, GdUfGOjb GdSjGOjIh GdehGRfI GdYGeI , COGA GdehGRfI GdYGeI h eDTQGJ bjGSg(B.s
Keywords: (3GdejRGfjIs; (3GdfabGJ GdYGeIs